2023
DOI: 10.3390/ijms241310896
|View full text |Cite
|
Sign up to set email alerts
|

Untangling Macropore Formation and Current Facilitation in P2X7

Abstract: Macropore formation and current facilitation are intriguing phenomena associated with ATP-gated P2X7 receptors (P2X7). Macropores are large pores formed in the cell membrane that allow the passage of large molecules. The precise mechanisms underlying macropore formation remain poorly understood, but recent evidence suggests two alternative pathways: a direct entry through the P2X7 pore itself, and an indirect pathway triggered by P2X7 activation involving additional proteins, such as TMEM16F channel/scramblase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Evidence of P2X7 direct macromolecule conductance exists, but multiple conductance states have not been observed at the single-channel level [ 16 , 17 ]. The accumulation of macromolecules with prolonged activation may be driven by an increase in the channel open probability (P o ) rather than by a fundamental change in single-channel conductance [ 18 , 19 ]. This model proposes that macromolecular conductance occurs in a typical open state at a very low permeability ratio.…”
Section: P2x7 Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of P2X7 direct macromolecule conductance exists, but multiple conductance states have not been observed at the single-channel level [ 16 , 17 ]. The accumulation of macromolecules with prolonged activation may be driven by an increase in the channel open probability (P o ) rather than by a fundamental change in single-channel conductance [ 18 , 19 ]. This model proposes that macromolecular conductance occurs in a typical open state at a very low permeability ratio.…”
Section: P2x7 Structure and Functionmentioning
confidence: 99%
“…This may be the foundation of the reversible permeabilization technique that relies on the activation of P2X7 channel dye uptake after prolonged activation in low Ca 2+ solutions, as removing extracellular Ca 2+ increases P2X7 activity [ 21 , 22 ]. However, P2X7 may also activate or recruit macropore-forming channels or hemi channels in biological settings (mechanisms reviewed in [ 19 ]). P2X7-mediated dye uptake has been reported to involve pannexin hemi channels and TMEM scramblase activity [ 18 , 23 , 24 ].…”
Section: P2x7 Structure and Functionmentioning
confidence: 99%
“…The P2X7R has some specific structural and functional characteristics that differentiate it from the other P2XR family members. This includes its ability to form macropores that are thought to be implicated in cell death mechanisms, prolonged activation and slower desensitisation kinetics, ectodomain shedding of cell-surface proteins, and a larger intracellular C-terminus which has been linked to pore formation and interactions with other proteins and intracellular signalling cascades (e.g., the extracellular signal-regulated kinases ([ERK]) pathway and activation of caspase-3) [42][43][44][45][46][47][48]. The N-terminus, in turn, has a specific interaction site for protein kinase C that is involved in the regulation of the Ca 2+ flow through the channel, controlling the receptor gating and facilitating its activation [49].…”
Section: The P2x7 Receptormentioning
confidence: 99%
“…Compared with other subtypes, P2X7R has a low sensitivity to ATP and possesses the ability not only to mediate ion channels but also to form nonselective large pores upon activation, thereby exerting bidirectional regulatory effects. 15 Additionally, a large number of studies have shown that P2X7R in living organisms exhibits obvious oncogene-like characteristics, and its abnormal expression and function are closely related to the occurrence and development of a variety of tumors. 16,17 Blockade or overstimulation of P2X7R has been proven to have an inhibitory effect on tumor cells and is a potential antitumor target.…”
Section: Introductionmentioning
confidence: 99%
“…Among these biomolecules, the P2X7 receptor (P2X7R) stands out due to its unique structure and function. Compared with other subtypes, P2X7R has a low sensitivity to ATP and possesses the ability not only to mediate ion channels but also to form nonselective large pores upon activation, thereby exerting bidirectional regulatory effects 15 . Additionally, a large number of studies have shown that P2X7R in living organisms exhibits obvious oncogene‐like characteristics, and its abnormal expression and function are closely related to the occurrence and development of a variety of tumors 16,17 .…”
Section: Introductionmentioning
confidence: 99%